2021
DOI: 10.3389/fphar.2020.611060
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Transcriptome Analysis Reveals the Inhibitory Function of Cinnamaldehyde in Non-Small Cell Lung Cancer

Abstract: Cinnamaldehyde (CA) is the main component extracted from the traditional Chinese medicine cinnamon. Recent studies revealed that CA has antiviral and anti-tumor effects. However, the effect and mechanism of CA on non-small cell lung cancer (NSCLC) through whole transcriptome sequencing integrated analysis have not been systematically investigated. In this study, whole transcriptome sequencing was used to identify differentially expressed messenger RNAs (mRNAs), micro RNAs (miRNAs), and long non-coding RNAs (ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…The antitumor effect of polysaccharides is a complex process, and various antitumor mechanisms correlated with each other [3]. Various antitumor mechanisms of polysaccharides have been reported previously [6,46,47]. Among them, enhancing host immune response and inducing tumor cell apoptosis has been considered as possible means of inhibiting tumor growth without harming the host [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antitumor effect of polysaccharides is a complex process, and various antitumor mechanisms correlated with each other [3]. Various antitumor mechanisms of polysaccharides have been reported previously [6,46,47]. Among them, enhancing host immune response and inducing tumor cell apoptosis has been considered as possible means of inhibiting tumor growth without harming the host [41].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis of A549 cells between SPP-0.7A treatment group and control group were performed by the previously described methods [47]. Briefly, A549 cells were cultured at 2 × 10 5 cell/well.…”
Section: Transcriptomic Assay and Analysismentioning
confidence: 99%
“…The formation and progression of tumors have been related to abnormal miRNAs expression levels [17][18][19][20][21]. MiRNA-483-5p express diversely and apply various consequences for an assortment of disease types.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in NSCLC showed that BTK inhibits proliferation, invasion and migration of tumor cells induced by cinnamaldehyde, which is extracted from cinnamon [53]. Moreover, another report showed that BTK-tyrosine kinase inhibitors may re-sensitize drug-resistant NSCLC to standard-of-care chemotherapy (cisplatin, gemcitabine and pemetrexed) [54].…”
Section: Discussionmentioning
confidence: 99%